Adult patients with tetralogy of fallot requiring pulmonary valve replacement: an expanding population. (22nd September 2015) - Steadman, CD; Hudsmith, LE; Hawkesford, S; Barron, D; Brawn, W; Jones, T; Clift, P; Thorne, SA
Abstract : Introduction: The population of patients surviving to adulthood with surgically corrected tetralogy of Fallot (TOF) is expanding. Adults now outnumber children with TOF. As a consequence, late complications are increasingly seen, most commonly pulmonary regurgitation (PR) potentially progressing to right ventricular failure, increasing symptoms, risk of arrhythmias and death. Timely pulmonary valve replacement (PVR) should prevent these. We are referring increasing numbers of patients for surgical PVR. In our adult congenital heart disease (ACHD) unit approximately three times as many PVR were performed in 2007 compared with 5 years ago. Demand for percutaneous PVR is likely to rise as technology develops to accommodate large right ventricular outflow tracts. We investigated the projected PVR requirements for our population of TOF patients. Methods and Results: We identified 338 patients with a mean age of 33 ± 12 years (range 17–68) with TOF from our ACHD database. 324 (95.9%) had a radical repair at a mean age of 7.6 ± 9.8 years (range 1–66 years). 10 (3%) patients are uncorrected with a significantly older mean age, 52.7 ± 15 years (range 32–76 years, p = 0.001 vs radical repair). Data are missing for four patients. 95 (29.3%) of repaired patients have received a PVR, whereas 229 (70.7%) have not. In the 229 patients who have yet to undergo PVR, the mean time since repair is 23.9 ± 8.5 years (range 2–46 years). Of these patients, 140 (61.1%) have severe PR by echocardiographic criteria, 36 (15.7%) moderate and 41 (17.9%) mild or less. Data are unavailable for 12 patients (5.2%). In the 95 patients with PVR, the mean time since repair is 19.2 ± 12.6 years (range 0–43 years). Six patients (6.3%) have had a second PVR. Five (5.2%) patients have severe PR, four (4.2%) moderate, and 82 (86.3%) mild or less. Data are missing in four (4.2%). Of patients with PVR and moderate or severe PR, the majority, seven, has homografts, one has a xenograft and data are missing in one. The time since PVR was significantly longer, 13 ± 4 years (range 5–18 years) versus 6 ± 6 years (range 0–27 years), p = 0.001 for mild PR (see fig). Conclusions: The most commonly performed operation in our ACHD unit is PVR. These data identify a significant number of patients with repaired TOF who have severe PR and will probably need PVR. The majority of children undergoing TOF repair still have a transannular patch, the main risk factor for late PR. Demand for PVR is therefore likely to continue to rise at least at the current rate. This will mean an increased workload for surgeons operating on ACHD patients, usually paediatric cardiac surgeons, but also for adult acquired heart disease units where the surgery and postoperative care takes place. Increasing use of percutaneous techniques may also help to meet this demand.